Status of Imperial Eagle in Iran - Mohammad A. Tabari (Пернатые хищники и их охрана)
Distribution and abundance of the Eastern Imperial Eagle (Aquila heliaca) in Iran: a scarce breeding bird in Caspian forests of central and eastern Alborz, and in the east of northern Khorasan. Conservation status: Globally has been listed as vulnerable (VU) in IUCN Red List and listed in CITES Appendix I.